Preparation and application of rare earth nickelate electronic phase change oxide curved surface coated composite material

By chemically adsorbing and growing a polycrystalline coating layer of rare earth nickelate on the surface of a curved core material, the problem of growing rare earth nickelate on a curved substrate is solved, enabling the application of composite materials in multi-dimensional functional responses, with functions such as intelligent electromagnetic shielding, optical design and camouflage, external field sensitive resistance and catalysis.

CN119264874AActive Publication Date: 2025-01-07UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411294005.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-07
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Existing technologies make it difficult to grow rare earth nickelate materials on curved substrates, which limits their application in composite materials, especially due to the influence of thermodynamic metastable phases and lattice distortion energy.

Method used

By using chemical adsorption to nucleate and grow a polycrystalline coating layer of rare earth nickelate on the surface of a curved core material, and by utilizing the coupling between the electronic phase transition characteristics of rare earth nickelate and the function of the core material, a composite material with multi-dimensional functional response can be prepared.

Benefits of technology

It realizes the synergistic application of the electronic phase transition properties of rare earth nickelates and the functions of core materials, enabling intelligent electromagnetic shielding, optical design and camouflage, external field sensitive resistors, logic electronic devices and catalytic functions under external field design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264874A_ABST
    Figure CN119264874A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing and applying a rare earth nickelate electronic phase change oxide curved surface coated composite material, which has the main conception that rare earth nickelate and a core material are designed in combination with an application scene, nucleation is carried out on the surface of the curved surface core material by utilizing the chemical adsorption effect of the rare earth nickelate, and a polycrystalline coating layer is grown; therefore, the coupling application of the electronic phase change characteristic of the rare earth nickelate and the function of the core material is realized. The method has the advantages that the rare earth nickelate can be adsorbed and wrapped on the surface of the core material with the micron-sized curvature radius, and a complex device can be designed according to an application scene in combination with electronic phase change characteristics. The metal-insulator conversion characteristic of the prepared composite material and the functional characteristic of the core material can realize multi-dimensional functional response under the regulation and control of external field design, and the composite material can be applied to the aspects of intelligent electromagnetic shielding, optical design and infrared camouflage, optical anti-counterfeiting, external field sensitive resistance, logic electronic devices and catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functional composite materials, and specifically relates to the preparation and application of rare earth nickelate electronic phase change oxide curved surface coated composite materials. Rare earth nickelate forms a coated polycrystalline layer by adsorbing a curved surface core with different crystal structures and no lattice matching relationship on the surface. The morphology of the curved surface core material can be determined by its properties and application scenarios. The surface is modified by a polycrystalline rare earth nickelate with reversible electronic phase change characteristics, thereby obtaining a composite material with both electronic phase change functional characteristics and shape adjustable characteristics. The technology provided by the present invention has potential application value in intelligent electromagnetic shielding, optical design and infrared camouflage, optical anti-counterfeiting, external field sensitive resistors, logic electronic devices, and catalysis. Background Art

[0002] Rare earth nickelate oxides have complex electronic and magnetic structures and exhibit metal-insulator phase transition characteristics triggered by characteristic temperature. Its material system mainly includes: 1) 113-type perovskite ReNiO3, where Re is a rare earth element other than La; 2) layered perovskite structure A n+1 Ni n O 3n+1 (n = 1, 2, 3), A is a rare earth element or a mixture of rare earth and alkaline earth elements.

[0003] Among them, ReNiO3 has a rich electronic structure. Under the triggering of characteristic temperature, characteristic pressure, polarization electric field, chemical or electrochemical hydrogenation, multiple electronic phase transitions can occur and cause sudden changes in the physical properties of the material, such as resistivity, dielectric constant and infrared reflectivity [1-3]. MIT ) can be continuously regulated in a wide temperature range of 100 to 600 K through the rare earth element composition. By using this property, the conductivity of the material can be regulated by temperature changes, thereby regulating the reflection of electromagnetic waves on the surface of the material [4], and obtaining an electromagnetic shielding material that can be intelligently regulated in multiple dimensions. When the temperature rises above the T of the rare earth nickelate MIT Transformed into the metal phase, the conductivity of the material is improved, the reflection and shielding efficiency of electromagnetic waves is improved, and the external field intelligent triggering of the electromagnetic shielding function is realized. The temperature does not exceed T MIT , rare earth nickelates are insulator phases, and electromagnetic waves can penetrate the material [5]. At the same time, the optical properties of rare earth nickelates before and after the phase transition can be used to design near-infrared intelligent detection and positioning and intelligent sensing temperature adaptive devices [6-9], or the anode catalytic oxidation properties of rare earth nickelates can be used for sewage treatment. The active oxygen physically adsorbed on the anode surface oxidizes the pollutants and eventually degrades them into substances with low biotoxicity or easily biodegradable. Therefore, ReNiO3 has potential application value in intelligent electromagnetic shielding, optical design and infrared camouflage, optical anti-counterfeiting, external field sensitive resistors, logic electronic devices, and catalysis. [10-12].

[0004] Rare earth nickel-based perovskites Re2NiO4 and Re3Ni2O7 both exhibit metal-insulator transition characteristics above room temperature, and their resistivity decreases first and then increases with increasing temperature. For La3Ni2O7, as the temperature increases, the semiconductor properties gradually transform into metallic properties, and its phase transition temperature is around 300 degrees Celsius

[13] . In addition, the rare earth nickel-based perovskite oxide La3Ni2O7 exhibits high-temperature superconductivity of 80 K under a pressure of 14 GPa, which provides help for further research on the mechanism of high-temperature superconductivity

[14] . And as the radius of the rare earth ion decreases, the phase transition temperature of Re2NiO4 will gradually increase. As for Re4Ni3O 10 , as the temperature increases, it shows a transition from a low-temperature metal phase to a high-temperature metal phase. 10 At a pressure of 43 GPa, low-temperature zero resistance appears at 20 K, showing a superconducting state. With the increase of pressure, the superconducting transition temperature further increases, and at 65 GPa, its superconducting transition temperature increases to 30 K

[14] . By doping its rare earth sites with other rare earth elements or alkaline earth metal elements, the Re of rare earth nickel-based perovskite can be regulated. n+1 Ni n O 3n+1 (n = 1, 2, 3) metal-insulator phase transition characteristics. In addition, other transition metal elements can be added to the nickel position to further regulate the Re of rare earth nickel-based perovskite n+1 Ni n O 3n+1 In addition to the electrical applications of 113-structured nickelates, rare earth nickel-based perovskites Re2NiO4 and Re3Ni2O7 also have similar electrical properties to 113-structured nickelates. 10 When the rare earth element is lanthanum, it has high-temperature superconducting properties under pressure, and has broad application prospects in the fields of energy, medicine, information, etc.

[0005] However, due to the high brittleness and hardness of rare earth nickel-based oxide materials, many applications of rare earth nickelate materials are currently based on two-dimensional growth on a flat substrate, and cannot achieve the coating growth of rare earth nickelate on an existing curved core. On the one hand, most rare earth nickelate materials are in a thermodynamically metastable phase state, and it is difficult to nucleate and grow on a substrate material that does not have a coherent relationship; on the other hand, when a curved substrate has a coherent relationship with the rare earth nickelate, the lattice distortion energy caused by the curvature radius of the substrate will further increase the forward Gibbs free synthesis energy of the material, thereby hindering the nucleation and growth of the material. In summary, the method of achieving the growth of rare earth nickelate materials on a curved substrate, thereby preparing a rare earth nickelate curved surface coating composite material, has great application value.

[0006] 【1】Escote M T, Da Silva A M L, Matos J D R, et al. General propertiesof polycrystalline Ln NiO3 ( Ln = Pr, Nd, Sm) compounds prepared throughdifferent precursors[J]. Journal of Solid State Chemistry, 2000, 151(2): 298-307.

[0007] 【2】Aydogdu G H, Ha S D, Viswanath B, et al. Epitaxy, strain, andcomposition effects on metal-insulator transition characteristics of SmNiO3thin films[J]. Journal of Applied Physics, 2011, 109(12): 124110

[0008] 【3】Kumar Y, Pratap Singh A, Sharma S K, et al. Irradiation inducedmodification in transport properties of LaNiO3 thin films: An x-rayabsorption study[J]. Applied Physics Letters, 2012, 101(11): 112103.

[0009] 【4】Bhattacharjee, Y.; Chatterjee, D.; Bose, S. Core–multishellheterostructure with excellent heat dissipation for electromagneticinterference shielding. ACS Appl. Mater. Interfaces 2018, 10 (36), 30762–30773

[0010] 【5】Bhattacharjee Y, Bose S. Core-shell nanomaterials for microwaveabsorption and electromagnetic interference shielding: a review [J]. AcsApplied Nano Materials, 2021, 4(2): 949-972.

[0011] 【6】 BESL P J, JAIN R C. Three-dimensional object recognition[J]. ACMComputing Sur veys1985,17(1):75-145.

[0012] 【7】CHAI Y. In-sensor computing for machine vision[J].Nature,2020,579(7797):32-33.

[0013] 【8】AFSHARI H, JACQUES L, BAGNATO L, et al. The PANOPTIC camera: aplenop tic sensor with real-time omnidirectional capability[J]. Journal ofSignal Processing Systems for Signal Image and Video Technology,2013,70(3):305-328.

[0014] 【9】SONG Y M, XIE Y, MALYARCHUK V, et al. Digital cameras with designsinspired by the arthropod eye[J]. Nature,2013,497(7447):95-99.

[0015]

[10] Schwanz D, Zhang Z, Narayanan B,et al. Perovskite nickelates aselectric-field sensors in salt water[J]. Nature, 2018, 553(7686): 68-72.

[0016]

[11] Zhang H T, Zuo F, Li F,et al. Perovskite nickelates as bio - electronic interfaces[J]. Nature Communications, 2019, 10(1): 1 - 7.

[0017]

[12] Zhang H T, Park T J, Zaluzhnyy I A,et al. Perovskite neural trees[J]. Nature Communications, 2020, 11(1): 1 - 9.

[0018]

[13] Sun H, Huo M, Hu X,et al. Signatures of superconductivity near 80 K in a nickelate under high pressure. Nature 621, 493–498 (2023).

[0019]

[14] G. Wang, N. Wang, J. Hou, L. Ma,et al.Pressure induced superconductivity in polycrystalline La3Ni2O 7. Physical Review X 14, 011040(2024)

[0020]

[15] Zhu Y, Peng D, Zhang E,et al. Superconductivity in pressurized trilayer La4Ni3O 10−δ single crystals. Nature 631, 531–536 (2024). Summary of the Invention

[0021] The present invention provides a method for preparing and applying a composite material based on a rare earth nickelate electronic phase change oxide curved surface coating, the main idea of ​​which is to design rare earth nickelate and core material through application scenarios, and utilize the chemical adsorption of rare earth nickelate to nucleate on the surface of the curved core material and grow into a polycrystalline coating layer, thereby realizing the coupling application of the electronic phase change characteristics of rare earth nickelate and the functions of the core material. The technology provided by the present invention enables the metal-insulator transition characteristics of the prepared composite material and the functional characteristics of the core material to achieve multi-dimensional functional response under the control of external field design, and can be applied to intelligent electromagnetic shielding, optical design and camouflage, external field sensitive resistors, logic electronic devices, and catalysis.

[0022] A method for preparing a rare earth nickelate electronic phase change oxide curved surface coated composite material, characterized in that the preparation of the composite material of the rare earth nickelate coated core comprises the following steps:

[0023] 1) Design the material composition, electronic phase transition characteristics, and synergistic mode of rare earth nickelates with the functions of the core materials according to the application scenarios, select the composition, surface shape and curvature, and size of the core materials, and improve their surface chemical adsorption on rare earth nickelates in the thermodynamically metastable phase in molten salts through surface modification;

[0024] 2) According to the stoichiometric ratio of the metal elements in the selected rare earth nickelate oxide, weigh the corresponding nickel and rare earth element precursor powders, add a certain proportion of molten salt and mix them evenly, apply the above-prepared mixed powder on the outside of the core material in step 1) or place the core material in the above-prepared mixed powder and compact it;

[0025] 3) Heating in a strong oxidizing atmosphere allows the precursor powder to be evenly mixed in the molten salt, and reducing the original positive Gibbs free energy of the rare earth nickelate through chemical adsorption on the surface of the core material, thereby nucleating and growing a rare earth nickelate polycrystalline coating layer on the surface of the core material. After cooling, the prepared composite material consisting of the rare earth nickelate polycrystalline layer coating the core material is taken out and washed with a solvent to remove the residual flux.

[0026] Furthermore, the core material components include aluminum oxide, titanium oxide, zirconium oxide, hafnium oxide, and garnet ferrite, and its morphology includes single crystal and polycrystalline ceramic body, and its curved surface shapes include sphere, ellipsoid, and cylinder, and its typical size range is 1 micron to 1 centimeter. The core material is characterized in that its surface has an adsorption effect on rare earth and nickel element precursors in molten salt, and is different from the crystal structure of rare earth nickelate and has no lattice matching relationship; the surface chemical environment of the above-mentioned core material can be modified by acid washing, alkali washing, heating in atmosphere, and surface doping process to improve the adsorption effect of the surface of rare earth nickelate, thereby promoting the rare earth nickelate in a thermodynamically metastable phase to form a coating layer in a polycrystalline form on the surface of the core material with a small radius of curvature.

[0027] Furthermore, the functional properties of the core material can be functionally designed or hollowed out to fill in the functional material body, so as to coordinate the composite of the functional properties of the rare earth nickelate coating layer; the functions of the core material include: high infrared emissivity, microwave absorption, electromagnetic induction, ferroelectricity, and high dielectric properties; the composite of the rare earth nickelate coating layer and the core functional properties mainly includes two ways: 1) using an external field to trigger the metal insulator phase change properties of the rare earth nickelate coating layer to achieve reversible shielding of the core function; 2) triggering the reversible triggering of the metal insulator phase change of the rare earth nickelate coating layer through the coupling of the core layer and the external field, thereby achieving a sudden change in the properties of the nickelate-coated core composite material. The external field forms of the electronic phase change properties of the rare earth nickelate coating layer include: ambient temperature, polarization electric field, chemical environment, stress, alternating electric field, alternating magnetic field. By adjusting the composition, radius of curvature, thickness of the rare earth nickelate coating layer and the composite design with the core material, the threshold range of the external field triggering the electronic phase change can be controlled; in a preferred example, polycrystalline neodymium samarium nickelate (Nd 0.4 Sm 0.6In another preferred embodiment, a 1 mm diameter Yttrium iron garnet ferrite ball coated with polycrystalline samarium nickelate (SmNiO3) is used. By changing the external microwave power, the temperature of the ferrite ball changes to trigger the nickelate metal insulator transition, thereby realizing the external field intelligent triggering of the electromagnetic shielding switch effect. In another preferred embodiment, a 1 mm diameter Zr-doped alumina ball coated with polycrystalline samarium nickelate (SmNiO3) has an increased transmittance and decreased emissivity of the coating layer to infrared light at a low temperature. When the temperature exceeds the phase transition temperature, the samarium nickelate is in a metallic phase, with an increased emissivity and a decreased transmittance. It can be applied to 8 to 140 °C temperature range. μm infrared camouflage; in another preferred embodiment, a yttrium iron garnet ferrite sphere with a diameter of 1 mm coated by polycrystalline praseodymium nickelate (PrNiO3) can control the electromagnetic shielding performance of the polycrystalline layer by temperature regulation, thereby controlling the resonant frequency of the yttrium iron garnet single crystal sphere resonator in a variable external magnetic field, which can be used for electronic countermeasures, electronic interference and anti-interference equipment; in another preferred embodiment, alumina spheres with a diameter of 10 microns coated by polycrystalline samarium nickelate (SmNiO3) are arranged and dispersed in an organic polymer with dielectric properties, and the organic polymer is solidified to form a polymer / composite sphere layer with a thickness of about 50 microns, which is composited between dielectric layers, and an electric field is applied to the electrode to form a polarization electric field between the layers to trigger the metal-insulator phase transition of the composite sphere, thereby achieving a sudden drop in resistivity, thereby achieving a breakdown effect. In another preferred embodiment, alumina spheres with a diameter of 30 microns coated by polycrystalline neodymium nickelate (NdNiO3) are arranged and dispersed in an organic polymer with conductive properties, and the organic polymer is solidified to form a polymer / composite sphere layer with a thickness of about 150 microns, which is compounded between dielectric layers, and stress is applied to the electrode to trigger the metal-insulator phase transition of the interlayer composite spheres, thereby achieving a sudden drop in resistivity. In another preferred embodiment, alumina composite spheres filled with magnetic particles coated by polycrystalline neodymium nickelate (NdNiO3) have a diameter of 100 microns. The principle that magnetic particles generate heat due to eddy currents and hysteresis under an alternating magnetic field is used to increase the core temperature to the NdNiO3 phase transition temperature, thereby triggering the outer metal-insulator transition, and realizing the coupling of the alternating magnetic field and the core functional body to trigger the electronic phase transition of rare earth nickelate.

[0028] Furthermore, the crystal structure of the rare earth nickelate includes 113-type perovskite ReNiO3 and layered perovskite Re n +1 Ni n O 3n+1 ; For ReNiO3, its rare earth element Re sites include: praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y) and the common occupation of the above elements in different proportions; For the layered perovskite structure Re n +1 Ni n O 3n+1, which mainly includes Re2NiO4, Re3Ni2O7, Re4Ni3O corresponding to n = 1, 2, 3 10 , and the rare earth element Re site thereof includes: lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y) and co-occupation of different ratios of the above elements; by changing the rare earth elements, the electronic band structure, metal-insulator phase transition characteristics, and hydrogen-induced electronic phase transition characteristics of rare earth nickelates can be adjusted; in a preferred example, polycrystalline neodymium samarium nickelate (Sm x Nd 1-x NiO3) (0 < x < 1) coated alumina spheres with a diameter of 500 microns achieve continuous regulation of the phase transition temperature in the range of 200 - 400 K. As the Sm content increases, the phase transition temperature increases linearly, where the phase transition temperature of Nd 0.4 Sm 0.6 NiO3 is close to room temperature; in another preferred example, the resistivity change before and after hydrogenation of ceramic fibers coated with polycrystalline europium nickelate (EuNiO3) is increased by 3 orders of magnitude compared to ceramic fibers with a curved surface radius of 10 microns coated with neodymium nickelate (NdNiO3); in another preferred example, polycrystalline double perovskite structure praseodymium-doped lanthanum nickelate (La 2.7 Pr 0.3 Ni2O7) coated alumina spheres with a diameter of 600 microns show an upward trend in resistivity compared to alumina spheres with a diameter of 600 microns coated with polycrystalline double perovskite structure lanthanum nickelate (La3Ni2O7);

[0029] Furthermore, the rare earth site of the above perovskite and layered perovskite can be partially replaced by alkaline earth element Ae, or the Ni-site can be partially replaced by other transition elements, so as to further regulate the valence state of nickel element, the electronic structure, electrical transport properties, and magnetism of the rare earth nickelate coating layer; wherein, the alkaline earth element Ae includes calcium, strontium, barium; Re 2-x Ae x NiO4, Re 3-x Ae x Ni2O7, Re 4-x Ae x Ni3O 10 The substitution range of alkaline earth elements in is 0 < x ≤ 1, and the substitution range of alkaline earth elements in Re 1-x Ae x NiO3 is 0 < x ≤ 0.3; the other transition elements are preferably manganese, iron, rhenium, vanadium, cobalt, and their substitution range for Ni-elements is greater than 0 and less than or equal to 30%; in a preferred example, polycrystalline double perovskite structure manganese-doped lanthanum nickelate (La3Mn 0.2 Ni1.8 Compared with the 300 μm diameter alumina sphere coated with polycrystalline double-layer perovskite structure lanthanum nickelate (La3Ni2O7), the resistivity of the 300 μm diameter alumina sphere is significantly increased; in another preferred embodiment, the polycrystalline single-layer perovskite structure cobalt-doped lanthanum nickelate (La2Co 0.1 Ni 0.9 O4) coated with alumina spheres with a diameter of 300 microns, the resistivity is significantly increased compared to alumina spheres with a diameter of 300 microns coated with polycrystalline single-layer perovskite structure lanthanum nickelate (La2NiO4); in another preferred embodiment, polycrystalline three-layer perovskite structure iron-doped lanthanum nickelate (La4Fe 0.3 Ni 2.7 O 10 ) coated with alumina spheres with a diameter of 300 μm compared to polycrystalline three-layer perovskite structure lanthanum nickel oxide (La4Ni3O 10 ) coated with an aluminum oxide sphere with a diameter of 300 microns, the resistivity increases; in another preferred embodiment, the resistivity of an aluminum oxide sphere with a diameter of 600 microns coated with a polycrystalline single-layer perovskite structure strontium-doped lanthanum nickelate (LaSrNiO4) is higher than that of an aluminum oxide sphere with a diameter of 600 microns coated with a polycrystalline single-layer perovskite structure strontium-doped praseodymium nickelate (PrSrNiO4), which increases by one order of magnitude;

[0030] Furthermore, the nickel and rare earth element precursor powders include nickel oxides, nitrates, acetates and carbonates, and rare earth element oxides, nitrates, acetates and carbonates. The specific molten salts include potassium chloride (KCl), sodium chloride (NaCl), lithium chloride (LiCl), potassium carbonate (K2CO3), sodium carbonate (Na2CO3) or their mixtures. The type and mixing ratio of the flux can be used to control the melting point of the flux and further design the reaction temperature. The ratio of the precursor to the molten salt ranges from 0.05 to 50, and the applied oxygen pressure ranges from 0.1 MPa to 100 MPa. By designing the molten salt composition, coordinating the reaction temperature and the oxygen pressure, the adsorption energy of the curved core in the molten salt on the rare earth nickelate precursor can be effectively controlled, thereby further controlling the crystallization quality, grain size, surface morphology of the polycrystalline coating layer, and the curvature radius of the curved core that can be wrapped. In a preferred example, for an alumina ball coated with polycrystalline neodymium nickelate (NdNiO3), when the radius of curvature of the alumina ball is 1 mm, potassium chloride is used as the molten salt, and the polycrystalline layer can be coated on the ball at 800 degrees Celsius and 7 MPa oxygen pressure, and the grains of the polycrystalline layer have regular shapes and uniform sizes; and when the radius of curvature of the alumina ball is 10 μm, in order to enable the polycrystalline layer to coat a smaller core ball, considering improving its surface adsorption, the molten salt is adjusted to a mass fraction of potassium chloride and lithium chloride of 1:1, the temperature and oxygen pressure are appropriately increased, and finally the curved surface coating is achieved at 1000 degrees Celsius and 10 MPa oxygen pressure, and the grains of the polycrystalline layer are more irregular in shape than the grains adsorbed by the 1 mm ball;

[0031] Furthermore, the prepared rare earth nickelate curved surface coated core composite material can be further arranged into an array, and the overall optical properties, microwave transmission properties, and DC and AC transport properties before and after the electronic phase transition can be adjusted by regulating the array arrangement mode; in a preferred embodiment, polycrystalline samarium neodymium nickelate (Nd 0.25 Sm 0.75 The high-precision, large-area multilayer array of alumina spheres with a diameter of 500 microns coated with NiO3) has a modulation effect on microwaves in the infrared-terahertz band, and the reflection and transmission frequencies can be regulated by the radius of the sphere surface and the composition and thickness of the rare earth nickelate coating layer; in another preferred embodiment, polycrystalline neodymium praseodymium nickelate (Pr 0.5 Nd 0.5 Alumina spheres with a diameter of 1 mm coated with NiO3 are arranged as bionic compound eye hemispheres. The process is to receive and sense the infrared signals of the surrounding environment and send them to the sensor, integrate the array and detector signal readout and some information processing functions into one device, which can form infrared environment position positioning information after processing, and detect the radiation intensity of the detection target through the curved ball sensing site, so as to realize the multi-dimensional acquisition of light field information and target distance characteristic information.

[0032] The application of the rare earth nickelate electronic phase change oxide curved surface coated composite material prepared according to the method as described above is characterized in that aluminum oxide, titanium oxide, zirconium oxide, hafnium oxide, and garnet ferrite with a certain curved surface shape are used as the core and their surface is modified to improve the surface adsorption effect on the specific crystal plane of the rare earth nickelate oxide, and after mixing it with rare earth and nickel element precursors and a specific flux, a rare earth nickelate polycrystalline layer is used to coat the surface of the above-mentioned core that does not have a crystal coherent relationship through a flux reaction; the metal-insulator transition characteristics of the prepared composite material and the functional characteristics of the core material can achieve multi-dimensional functional response under the design and regulation of an external field, and the shell layer of the composite material with a core-shell structure has the functional characteristics of electronic phase change under external field triggering, and can cooperate with the functional characteristics of the core material, thereby realizing intelligent electromagnetic shielding, optical design and infrared camouflage, optical anti-counterfeiting, external field sensitive resistors, logic electronic devices, and catalytic functions.

[0033] After extensive and in-depth research, the present invention has obtained the preparation and application of rare earth nickelate electronic phase change oxide curved surface coating composite materials. The present invention reduces the forward Gibbs free energy of rare earth nickelate by chemical adsorption, realizes the formation of a coating polycrystalline layer on the curved surface core with different crystal structures and no lattice matching relationship, and realizes the coupling application of the core material properties and the rare earth nickelate properties by designing the core material morphology, changing the surface treatment process, and doping the coating layer components; it has application value in intelligent electromagnetic shielding, optical design and infrared camouflage, optical anti-counterfeiting, external field sensitive resistors, logic electronic devices, catalysis and high temperature superconductivity. Compared with previous composite technologies, the technology provided by the present invention has the advantages of realizing the coating of curved surface cores with inorganic functional materials and designing complex devices in combination with electronic phase change characteristics according to application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a photograph of alumina (Al2O3) pellets coated with neodymium nickelate (NdNiO3) using the method of the present invention.

[0035] Figure 2 The temperature resistance curve of alumina (Al2O3) spheres coated with neodymium nickelate (NdNiO3) by the method of the present invention is shown.

[0036] Figure 3 The figure is the temperature resistance curve of ceramic fiber coated with samarium nickelate (SmNiO3) by the method of the present invention.

[0037] Figure 4 In order to coat yttrium iron garnet (Y3Fe5O 12 ) The resistance-temperature relationship curve of the ball.

[0038] Figure 5The present invention provides a resistance-temperature relationship curve of a small aluminum oxide (Al2O3) ball coated with a single-layer perovskite structure lanthanum nickelate (La2NiO4) using the method of the present invention.

[0039] Figure 6 The present invention provides a resistance-temperature curve of a small aluminum oxide (Al2O3) ball coated with double-layer perovskite structure lanthanum nickelate (La3Ni2O7) using the method of the present invention.

[0040] Figure 7 The present invention provides a grazing incidence X-ray diffraction pattern of aluminum oxide (Al2O3) coated with neodymium nickelate (NdNiO3) using the method of the present invention.

[0041] Figure 8 The following is a scanning electron microscope image of a 40 micron diameter aluminum oxide (Al2O3) sphere coated with samarium nickelate (SmNiO3) using the method of the present invention.

[0042] Fig. 9 This is a scanning electron microscope image of a 3 micron diameter aluminum oxide (Al2O3) ceramic fiber coated with samarium nickelate (SmNiO3) using the method of the present invention.

[0043] Fig.10 The present invention is a schematic diagram of the polarization electric field triggering principle of coating the dielectric layer of the curved ball array with rare earth nickelate electronic phase change oxide using the method of the present invention.

[0044] Fig.11 The schematic diagram of the stress triggering principle of coating the piezoelectric layer of a curved sphere with rare earth nickelate electronic phase change oxide using the method of the present invention is shown.

[0045] Fig.12 This is a schematic diagram of the terahertz microwave modulation principle of a quasi-photonic crystal array of curved small balls coated with rare earth nickelate electronic phase change oxides according to the method of the present invention.

[0046] Fig.13 This is a schematic diagram of infrared position detection and positioning sensing using a rare earth nickelate electronic phase change oxide coated curved ball compound eye array in the method of the present invention. DETAILED DESCRIPTION

[0047] Unless otherwise specified, the various raw materials of the present invention can be obtained by commercially available or by conventional methods in the art. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the method of the present invention.

[0048] Other aspects of the present invention will be apparent to those skilled in the art in view of the disclosure herein.

[0049] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0050] Test method: XRD, SEM, CTA and PPMS were used to characterize the prepared materials. The characterization methods were carried out according to the general standards in the field.

[0051] Example-1:

[0052] In order to realize the intelligent regulation of the infrared emissivity of composite materials in the atmospheric window band, Nd x Sm 1-x NiO3 (0≤x≤1) coated ultra-white alumina spheres with high infrared emissivity in the atmospheric window band. Ultra-white alumina spheres with a diameter of 500 μm are used as the core material, nickel oxide, neodymium oxide, and samarium oxide are used as precursors, and potassium chloride is used as molten salt. After reacting at 7 MPa oxygen pressure and 800 degrees Celsius for 24 hours, the spheres are taken out. The resulting composite material is shown in the photo Figure 1 The resistivity-temperature relationship is shown in Figure 2 As shown, the grazing incidence X-ray diffraction pattern is as follows Figure 7 Nd with polycrystalline structure 0.4 Sm 0.6 NiO3 is evenly coated on the surface of the ultra-white alumina sphere, and the whole sphere exhibits metal-insulator phase transition characteristics at 302 K. When the temperature is lower than 302 K, Nd 0.4 Sm 0.6 NiO3 has high infrared transmittance in the atmospheric window band of interest, and since alumina has high infrared emission in this band, the composite material exhibits overall high radiation characteristics; and when the temperature is higher than 302 K, Nd 0.4 Sm 0.6 NiO3 has low infrared transmittance in the atmospheric window band of interest, which suppresses the infrared emission of ultra-white alumina and makes the composite material present an overall low-radiation characteristic.

[0053] Example-2:

[0054] In order to achieve the temperature-induced infrared color-tuning characteristics in a wide temperature range of 100-600 K, a series of PrNiO3, NdNiO3, Nd 0.5 Sm 0.5 NiO3、Nd 0.4 Sm 0.6NiO3, SmNiO3, EuNiO3, and GdNiO3 are coated with Zr-doped alumina spheres with a curvature radius of 10 μm to 1 mm, respectively. The surface electron scanning micrograph of the alumina sphere with a diameter of 40 μm coated with SmNiO3 is shown in the figure. Figure 8 As shown. To prepare PrNiO3 coated Zr-doped alumina spheres with a diameter of 600 μm, praseodymium oxide and nickel oxide are used as precursors, potassium carbonate is used as molten salt, and the reaction is carried out at 4 MPa and 800 degrees Celsius for 24 hours; to prepare NdNiO3 coated Zr-doped alumina spheres with a diameter of 100 μm, neodymium oxide and nickel oxide are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 5 MPa and 800 degrees Celsius for 24 hours; to prepare SmNiO3 coated Zr-doped alumina spheres with a diameter of 800 μm, samarium nitrate and nickel nitrate are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 7 MPa and 900 degrees Celsius for 36 hours; to prepare EuNiO3 coated Zr-doped alumina spheres with a diameter of 1 mm, europium oxide and nickel oxide are used as precursors, lithium chloride and sodium chloride are used as molten salts, and the reaction is carried out at 12 MPa and 900 degrees Celsius for 36 hours. In order to prepare GdNiO3 coated Zr-doped alumina beads with a diameter of 1mm, gadolinium oxide and nickel oxide are used as precursors, lithium chloride is used as molten salt, and the reaction is carried out at 15 MPa and 900 degrees Celsius for 48 hours. The above rare earth nickelate presents an insulator phase when the temperature is lower than the metal insulator phase transition temperature, which has high infrared reflectivity and low infrared transmittance; and presents a metallic phase when the temperature is higher than the metal insulator phase transition temperature, which has low infrared reflectivity and high infrared transmittance. The above rare earth nickelate coated Zr-doped alumina beads with different rare earth elements and metal insulator phase transition temperatures are arranged into a photonic crystal plane array, and the high and low change patterns of infrared reflectivity of the overall plane at different temperatures are controlled by adjusting the arrangement mode, thereby realizing the infrared imaging difference of different plane pixels under temperature triggering, and realizing anti-counterfeiting, optical design and infrared camouflage functions.

[0055] Example-3:

[0056] In order to realize the self-protection function of ferrite frequency modulation devices, PrNiO3, NdNiO3, Nd x Sm 1-x NiO3 (x=0.1, 0.2, 0.3, 0.4), SmNiO3, EuNiO3, and GdNiO3 are coated with yttrium iron garnet (YIG) spheres with a curvature radius of 50μm to 8mm, respectively. The resistance-temperature relationship of the YIG sphere with a diameter of 200μm coated by PrNiO3 is as follows: Figure 4To prepare PrNiO3-coated YIG beads with a diameter of 200 μm, nickel oxide and praseodymium oxide were used as precursors, potassium chloride was used as molten salt, and the reaction was carried out at 6 MPa and 800 degrees Celsius for 24 hours; to prepare NdNiO3-coated YIG beads with a diameter of 150 μm, nickel oxide and samarium oxide were used as precursors, potassium chloride was used as molten salt, and the reaction was carried out at 6 MPa and 800 degrees Celsius for 30 hours; to prepare Nd x Sm 1-x NiO3 (x = 0.1, 0.2, 0.3, 0.4) coated YIG beads with a diameter of 100 μm, using nickel oxide, neodymium oxide, samarium oxide as precursors, potassium chloride as molten salt, and reacting at 6 MPa 800 degrees Celsius for 36 hours; to prepare SmNiO3 coated YIG beads with a diameter of 700 μm, using samarium nitrate and nickel nitrate as precursors, potassium chloride as molten salt, and reacting at 9 MPa 900 degrees Celsius for 36 hours; to prepare EuNiO3 coated YIG beads with a diameter of 2 mm, using europium acetate and nickel acetate as precursors, sodium chloride as molten salt, and reacting at 10 MPa 900 degrees Celsius for 36 hours. To prepare GdNiO3 coated YIG beads with a diameter of 1 mm, using gadolinium nitrate and nickel nitrate as precursors, lithium chloride as molten salt, and reacting at 12 MPa 1000 degrees Celsius for 48 hours. Under the action of external microwave power, YIG heats up and the temperature rises below the metal-insulator phase transition temperature. The rare earth nickelate presents an insulator phase and has no obvious shielding against external microwaves. When the temperature rises above the metal-insulator phase transition temperature, the rare earth nickelate transforms into a metal phase, and the reflection and shielding performance against microwaves is improved. Therefore, the self-protection function of the ferrite frequency modulation device can be realized, and the critical power density can be adjusted by controlling the metal-insulator phase transition temperature of the coating layer by regulating the rare earth element composition.

[0057] Example-4:

[0058] In order to realize the sudden change thermistor device applied in different scenarios, a series of Pr x Sm 1-x NiO3 (0≤x≤1), Pr x Nd 1-x NiO3 (0≤x≤1), Nd x Sm 1-x NiO3 (0≤x≤1), Sm x Eu 1-x NiO3 (0≤x≤1) and other rare earth element doped nickelates are coated with alumina, zirconium oxide, hafnium oxide small balls or small cylinders with a curvature radius of 5μm to 5mm. x Sm 1-x NiO3 coating layer, using praseodymium oxide, nickel oxide, samarium oxide as precursors, potassium chloride as molten salt, reacting at 6 MPa and 900 degrees Celsius for 20 hours;x Nd 1-x NiO3 coating layer, using neodymium acetate, praseodymium acetate, nickel acetate as precursors, potassium chloride as molten salt, reacting at 6 MPa and 950 degrees Celsius for 24 hours; x Sm 1-x The NiO3 coating layer uses samarium nitrate, neodymium nitrate, and nickel nitrate as precursors and potassium carbonate as molten salt, and reacts at 7 MPa and 900 degrees Celsius for 36 hours; x Eu 1-x The NiO3 coating layer uses europium oxide, samarium oxide, and nickel oxide as precursors, lithium chloride and sodium chloride as molten salts, and reacts at 9 MPa and 900 degrees Celsius for 36 hours. The metal-insulator phase transition temperature range of the prepared rare earth nickelates doped with different rare earth elements and coated with aluminum oxide, zirconium oxide, and hafnium oxide small balls or small cylinders is: 100-600K. With the decrease of the rare earth element ion radius, the phase transition temperature of the rare earth nickelates gradually increases and the degree of resistivity change caused by the metal-insulator phase transition gradually increases. In summary, by changing the type and doping amount of rare earth elements, the electronic phase transition temperature range of rare earth nickelates can be continuously regulated, and the sudden change temperature of thermistors can be accurately designed according to the application scenario.

[0059] Example-5:

[0060] In order to realize infrared camouflage technologies such as thermal deception and optical design anti-counterfeiting, the material is driven by temperature to undergo a reversible phase change, thereby dynamically controlling the material's own infrared emissivity. x Sm 1-x NiO3 (x = 0.1, 0.2, 0.3, 0.4, 0.5), SmNiO3, EuNiO3, GdNiO3 are coated with titanium dioxide beads with a curvature radius of 50μm to 1mm. x Sm 1-xTo prepare NiO3 (x=0.1, 0.2, 0.3, 0.4, 0.5) coated titanium dioxide spheres with a diameter of 500μm, nickel oxide, neodymium oxide, and samarium oxide are used as precursors, and potassium chloride is used as molten salt, and the reaction is carried out at 7 MPa and 880 degrees Celsius for 30 hours; to prepare SmNiO3 coated titanium dioxide spheres with a diameter of 800μm, samarium nitrate and nickel nitrate are used as precursors, and potassium chloride is used as molten salt, and the reaction is carried out at 7 MPa and 900 degrees Celsius for 40 hours; to prepare EuNiO3 coated titanium dioxide spheres with a diameter of 900μm, europium oxide and nickel oxide are used as precursors, and sodium chloride is used as molten salt, and the reaction is carried out at 7 MPa and 900 degrees Celsius for 42 hours. To prepare GdNiO3-coated titanium dioxide spheres with a diameter of 1 mm, gadolinium nitrate and nickel nitrate were used as precursors, lithium chloride was used as molten salt, and the reaction was carried out at 10 MPa and 950 degrees Celsius for 48 hours. The infrared emission characteristics of rare earth nickelate metal insulators within the phase transition temperature range are independent of temperature, and the target emissivity is adaptively controlled to adapt to temperature changes in different regions, thereby realizing intelligent dynamic infrared camouflage of the composite material.

[0061] Example-6:

[0062] In order to realize the application of composite materials in marine electric field sensing or neuron logic devices, ceramic fibers with fiber diameters of 1 μm to 50 μm are coated with NdNiO3, SmNiO3, and EuNiO3 respectively. The resistivity-temperature relationship of ceramic fibers with a fiber diameter of 3 μm coated with SmNiO3 is as follows: Figure 3 Scanning electron microscope photos are shown in Fig. 9 As shown. To prepare the NdNiO3 coating, neodymium nitrate and nickel nitrate are used as precursors, sodium carbonate is used as molten salt, and the reaction is carried out at 3.5 MPa and 850 degrees Celsius for 20 hours; to prepare the SmNiO3 coating, samarium nitrate and nickel nitrate are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 6.5 MPa and 860 degrees Celsius for 36 hours; to prepare the EuNiO3 coating, europium acetate and nickel acetate are used as precursors, lithium chloride and sodium chloride are used as molten salt, and the reaction is carried out at 8 MPa and 900 degrees Celsius for 40 hours. After the rare earth nickelate is hydrogenated, the Ni based 3+ The electron roving state becomes based on Ni 2+ The electron localization state increases the resistivity by several orders of magnitude, and the proton conductivity is maintained at a high level while the hydrogenation process is reversible. The ultra-high sensitivity brought by the tiny size of hydrogen ions enables it to respond to external signals ultra-fast and accurately. After applying an electrical bias through proton conduction, the rare earth nickelate resistor responds, thereby realizing the application of composite materials in the field of marine sensors or neuron logic devices.

[0063] Example-7:

[0064] In order to realize thermistor devices for application in different scenarios, a series of nickelates doped with rare earth elements or alkaline earth elements in single-layer perovskite structure nickelates (Re2NiO4) are used to coat aluminum oxide, zirconium oxide, hafnium oxide small balls or small cylinders with a curvature radius of 5μm to 5mm. To prepare the LaPrNiO4 coating layer, lanthanum oxide, praseodymium oxide, and nickel oxide are used as precursors, potassium chloride is used as molten salt, and reacted at 0.1 MPa oxygen pressure and 1200 degrees Celsius for 24 hours; to prepare the PrSrNiO4 coating layer, strontium acetate, nickel acetate, and praseodymium acetate are used as precursors, potassium chloride is used as molten salt, and reacted at 0.1 MPa oxygen pressure and 1200 degrees Celsius for 24 hours; to prepare the NdSrNiO4 coating layer, neodymium oxide, strontium oxide, and nickel oxide are used as precursors, potassium carbonate is used as molten salt, and reacted at 0.1 MPa oxygen pressure. To prepare the EuSrNiO4 coating layer, europium oxide, strontium oxide and nickel oxide are used as precursors, potassium carbonate is used as molten salt, and the reaction is carried out at 0.5 MPa oxygen pressure and 1200 degrees Celsius for 36 hours; to prepare the GaBaNiO4 coating layer, gadolinium oxide, barium oxide and nickel oxide are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 1 MPa oxygen pressure and 1300 degrees Celsius for 24 hours; by changing the type of elements and the amount of doping, the electronic phase transition temperature range of the coating layer can be controlled.

[0065] Example-8:

[0066] To realize a sensor device that can monitor human body temperature, Nd 0.5 Sm 0.5 NiO3 coated ceramic fibers with a fiber diameter of 1 μm to 50 μm. 0.5 Sm 0.5 The NiO3 coating layer uses nickel oxide, neodymium oxide, and samarium oxide as precursors and potassium chloride as molten salt, and reacts at 6 MPa and 800 degrees Celsius for 36 hours. The flexible sensor with ceramic fiber fabric as the substrate corresponds to different resistivity changes at different temperatures, and its temperature sensitivity around the phase transition temperature is particularly accurate. It can monitor external stimuli and convert them into accurately identifiable electrical signals, providing a basis for the digitization of various application scenarios.

[0067] Example-9:

[0068] In order to achieve the treatment of industrial-grade wastewater by anodic oxidation adsorption of active oxygen, a series of PrNiO3, NdNiO3, SmNiO3, EuNiO3, GdNiO3, DyNiO3, and HoNiO3 were used to coat alumina balls with an average diameter of 1 mm. To prepare the PrNiO3 coating layer, praseodymium oxide and nickel oxide are used as precursors, potassium carbonate is used as molten salt, and the reaction is carried out at 4 MPa and 800 degrees Celsius for 24 hours; to prepare the NdNiO3 coating layer, neodymium oxide and nickel oxide are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 5 MPa and 800 degrees Celsius for 24 hours; to prepare the SmNiO3 coating layer, samarium nitrate and nickel nitrate are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 7 MPa and 900 degrees Celsius for 36 hours; to prepare the EuNiO3 coating layer, europium oxide and nickel oxide are used as precursors, lithium chloride and sodium chloride are used as molten salts, and the reaction is carried out at 7 MPa and 900 degrees Celsius for 36 hours. To prepare the GdNiO3 coating, gadolinium oxide and nickel oxide are used as precursors, lithium chloride is used as molten salt, and the reaction is carried out at 9 MPa and 900 degrees Celsius for 48 hours; to prepare the DyNiO3 coating, dysprosium nitrate and nickel nitrate are used as precursors, lithium chloride and potassium chloride mixture is used as molten salt, and the reaction is carried out at 10 MPa and 900 degrees Celsius for 48 hours; to prepare the HoNiO3 coating, holmium nitrate and nickel nitrate are used as precursors, lithium chloride is used as molten salt, and the reaction is carried out at 10 MPa and 900 degrees Celsius for 48 hours. According to industrial wastewater of different temperatures, suitable rare earth nickelates are selected for anodic oxidation catalysis. The active oxygen physically adsorbed on the anode surface of the rare earth nickelates in the water purification water filter box filled with rare earth nickelate coated alumina beads oxidizes the pollutants, and finally degrades them into substances with low biological toxicity or easily biodegradable, or even directly mineralizes them into inorganic substances, thereby achieving the purpose of industrial wastewater treatment.

[0069] Example-10:

[0070] In order to realize superconducting material related devices for application in different scenarios, La3Ni2O7 and La4Ni3O 10 Superconducting properties under pressure. Layered perovskite structure nickelates are coated with aluminum oxide, zirconium oxide, hafnium oxide spheres or small cylinders with a curvature radius of 5μm to 5mm. To prepare the La3Ni2O7 coating layer, lanthanum oxide and nickel oxide are used as precursors, potassium chloride is used as molten salt, and reacted at 0.1 MPa oxygen pressure and 1100 degrees Celsius for 24 hours; to prepare La4Ni3O 10 The coating layer uses lanthanum acetate and nickel acetate as precursors and potassium chloride as molten salt, and reacts under 0.1 MPa oxygen pressure and 1000 degrees Celsius for 24 hours; by changing the ambient pressure, the temperature range in which the coating layer undergoes zero-resistance superconductivity can be controlled.

[0071] Example-11:

[0072] In order to realize the sudden change thermistor device for application in different scenarios, La3Ni2O7 is used to achieve a sharper temperature-triggered resistivity sudden change characteristic than the heavy rare earth component 113-type rare earth nickel-based perovskite oxide in the high temperature range. A series of nickelates doped with rare earth elements or alkaline earth elements, or transition elements doped with nickel, are coated with alumina, zirconium oxide, hafnium oxide spheres or small cylinders with a curvature radius of 5μm to 5mm. The resistance-temperature relationship of the alumina sphere with a diameter of 200μm coated with La3Ni2O7 is as follows: Figure 6 As shown. To prepare La 2.7 Pr 0.3 To prepare the Ni2O7 coating layer, lanthanum oxide, praseodymium oxide, and nickel oxide are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 0.1 MPa oxygen pressure and 1100 degrees Celsius for 24 hours; to prepare the La3Ni2O7 coating layer, lanthanum acetate and nickel acetate are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 0.1 MPa oxygen pressure and 1100 degrees Celsius for 24 hours; to prepare the La 3-x Bi x The Ni2O7 coating layer uses lanthanum oxide, bismuth oxide, and nickel oxide as precursors and potassium carbonate as molten salt, and reacts at 0.1 MPa oxygen pressure and 1100 degrees Celsius for 36 hours. As the Bi doping amount increases, La 3-x Bi x The metal-insulator transition temperature of Ni2O7 gradually decreases. By changing the type of elements and the amount of doping, the electronic phase transition temperature range of the coating layer can be adjusted to achieve precise design of the thermistor mutation temperature according to the application scenario.

[0073] Example-12:

[0074] In order to realize thermistor devices, single-layer perovskite structure nickelate La2NiO4 is used to coat aluminum oxide, zirconium oxide, hafnium oxide small balls or small cylinders with a curvature radius of 5μm to 5mm. The resistance-temperature relationship of La2NiO4 coated aluminum oxide small balls with a curvature radius of 20μm is as follows: Figure 5 To prepare the La2NiO4 coating, lanthanum oxide and nickel oxide are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 0.1 MPa oxygen pressure and 1200 degrees Celsius for 30 hours; by changing the growth time, the electronic phase transition temperature range of the coating can be controlled.

[0075] Example-13:

[0076] To realize a thermistor device for applications in different scenarios, nickelates with a single-layer perovskite structure (Re2NiO4) doped with a series of rare earth elements or alkaline earth elements at the rare earth sites are used to coat alumina, zirconia, hafnium oxide spheres or small cylinders with a curvature radius of 5 μm to 5 mm. To prepare the La2Co x Ni 1-x O4 (0 < x ≤ 0.3) coating, lanthanum oxide, cobalt oxide, and nickel oxide are used as precursors, potassium chloride is used as a molten salt, and the reaction is carried out at an oxygen pressure of 0.1 megapascal and a temperature of 1200 °C for 24 hours; To prepare the La2Fe x Ni 1-x O4 (0 < x ≤ 0.3) coating, iron acetate, nickel acetate, and lanthanum acetate are used as precursors, potassium chloride is used as a molten salt, and the reaction is carried out at an oxygen pressure of 0.1 megapascal and a temperature of 1200 °C for 24 hours; To prepare the La2V x Ni 1-x O4 (0 < x ≤ 0.3) coating, lanthanum oxide, vanadium oxide, and nickel oxide are used as precursors, potassium carbonate is used as a molten salt, and the reaction is carried out at an oxygen pressure of 0.1 megapascal and a temperature of 1350 °C for 36 hours; To prepare the La2Mn x Ni 1-x O4 (0 < x ≤ 0.3) coating, manganese oxide, lanthanum oxide, and nickel oxide are used as precursors, potassium carbonate is used as a molten salt, and the reaction is carried out at an oxygen pressure of 0.5 megapascal and a temperature of 1460 °C for 36 hours; By changing the type of elements, doping amount, and growth time, the electronic phase transition temperature range of the coating layer can be regulated.

[0077] Example - 14:

[0078] To realize a thermistor device for applications in different scenarios, nickelates with a double-layer perovskite structure (Re3Ni2O7) doped with a series of rare earth elements or alkaline earth elements at the rare earth sites are used to coat alumina, zirconia, hafnium oxide spheres or small cylinders with a curvature radius of 5 μm to 5 mm. To prepare the La3Co x Ni 2-x O7 (0 < x ≤ 0.3) coating, lanthanum oxide, cobalt oxide, and nickel oxide are used as precursors, potassium chloride is used as a molten salt, and the reaction is carried out at an oxygen pressure of 0.1 megapascal and a temperature of 1180 °C for 24 hours; To prepare the La3Fe x Ni 2-x O7 (0 < x ≤ 0.3) coating, iron acetate, nickel acetate, and lanthanum acetate are used as precursors, potassium chloride is used as a molten salt, and the reaction is carried out at an oxygen pressure of 0.1 megapascal and a temperature of 1200 °C for 24 hours; To prepare the La3V x Ni 2- xThe O7 (0 < x ≤ 0.3) coating layer is prepared by using lanthanum oxide, vanadium oxide, and nickel oxide as precursors and potassium carbonate as a molten salt, reacting at 0.1 megapascal oxygen pressure and 1350 degrees Celsius for 36 hours; for the preparation of La3Mn x Ni 2-x The O7 (0 < x ≤ 0.3) coating layer is prepared by using manganese oxide, lanthanum oxide, and nickel oxide as precursors and potassium carbonate as a molten salt, reacting at 0.5 megapascal oxygen pressure and 1200 degrees Celsius for 36 hours; the electronic phase transition temperature range of the coating layer can be regulated by changing the types of elements, doping amounts, and growth times.

[0079] Example - 15:

[0080] To realize thermistor devices applied in different scenarios, a series of nickelates with rare earth elements or alkaline earth elements doped in the rare earth sites of the perovskite - structured nickelate of three layers are used to coat alumina, zirconia, hafnium oxide spheres or small cylinders with a curvature radius of 5 μm to 5 mm. For the preparation of La4Co 10 ) x Ni 3-x O 10 (0 < x ≤ 0.3) coating layer, using lanthanum oxide, cobalt oxide, and nickel oxide as precursors, potassium chloride as a molten salt, reacting at 0.1 megapascal oxygen pressure and 1300 degrees Celsius for 24 hours; for the preparation of La4Fe x Ni 3-x O 10 (0 < x ≤ 0.3) coating layer, using iron acetate, nickel acetate, and lanthanum acetate as precursors, potassium chloride as a molten salt, reacting at 0.1 megapascal oxygen pressure and 1500 degrees Celsius for 24 hours; for the preparation of La3V x Ni 3- x O 10 (0 < x ≤ 0.3) coating layer, using lanthanum oxide, vanadium oxide, and nickel oxide as precursors, potassium carbonate as a molten salt, reacting at 0.1 megapascal oxygen pressure and 1200 degrees Celsius for 36 hours; for the preparation of La2Mn x Ni 1-x O4 (0 < x ≤ 0.3) coating layer, using manganese oxide, lanthanum oxide, and nickel oxide as precursors, potassium carbonate as a molten salt, reacting at 0.5 megapascal oxygen pressure and 1200 degrees Celsius for 36 hours; the resistance - temperature relationship change range of the coating layer can be regulated by changing the types of elements, doping amounts, and growth times.

[0081] Example - 16:

[0082] In order to realize the application of the metal-insulator phase change process of composite spheres triggered by polarization electric field, a series of PrNiO3, NdNiO3, SmNiO3, EuNiO3, and GdNiO3 are used to coat a number of alumina spheres with an average diameter of 10μm, which are arranged and dispersed in an organic polymer with dielectric properties. The organic polymer is solidified to form a polymer / composite sphere layer with a thickness of about 50 microns, which is compounded between dielectric layers. An electric field is applied to the electrode to form a polarization electric field between the layers to trigger the metal-insulator phase change of the composite sphere, thereby achieving a sudden drop in resistivity and achieving a breakdown effect. The principle diagram is shown in the figure. Fig.10 To prepare the PrNiO3 coating layer, praseodymium oxide and nickel oxide are used as precursors, potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 5 MPa and 800 degrees Celsius for 24 hours; to prepare the NdNiO3 coating layer, neodymium nitrate and nickel nitrate are used as precursors, potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 6 MPa and 820 degrees Celsius for 36 hours; to prepare the SmNiO3 coating layer, samarium nitrate and nickel nitrate are used as precursors, potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 6.5 MPa and 860 degrees Celsius. Celsius conditions for 36 hours; to prepare the EuNiO3 coating layer, europium acetate and nickel acetate are used as precursors, potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 7 MPa and 900 degrees Celsius for 36 hours; to prepare the GdNiO3 coating layer, gadolinium oxide and nickel oxide are used as precursors, and a mixture of lithium chloride and potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 7 MPa and 900 degrees Celsius for 48 hours; by changing the type of elements, doping amount and growth time, the electronic phase transition temperature range of the coating layer can be regulated.

[0083] Example-17:

[0084] In order to realize the application of stress-triggered metal-insulator phase change of composite spheres, a series of PrNiO3, NdNiO3, SmNiO3, EuNiO3, and GdNiO3 are used to coat a number of alumina spheres with an average diameter of 30μm, which are arranged and dispersed in an organic polymer with conductive properties. The organic polymer is solidified to form a polymer / composite sphere layer with a thickness of about 150 microns, which is composited between dielectric layers. Stress is applied to the electrode to trigger the metal-insulator phase change of the interlayer composite spheres, achieving a sudden drop in resistivity. The principle diagram is shown in the figure. Fig.11To prepare the PrNiO3 coating layer, praseodymium oxide and nickel oxide are used as precursors, potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 5 MPa and 800 degrees Celsius for 24 hours; to prepare the NdNiO3 coating layer, neodymium nitrate and nickel nitrate are used as precursors, potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 6 MPa and 820 degrees Celsius for 36 hours; to prepare the SmNiO3 coating layer, samarium nitrate and nickel nitrate are used as precursors, potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 6.5 MPa and 860 degrees Celsius. Celsius conditions for 36 hours; to prepare the EuNiO3 coating layer, europium acetate and nickel acetate are used as precursors, potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 7 MPa and 900 degrees Celsius for 36 hours; to prepare the GdNiO3 coating layer, gadolinium oxide and nickel oxide are used as precursors, and a mixture of lithium chloride and potassium chloride is used as molten salt, and several small balls are placed in the precursor powder, and reacted at 7 MPa and 900 degrees Celsius for 48 hours; by changing the type of elements, doping amount and growth time, the electronic phase transition temperature range of the coating layer can be regulated.

[0085] Example-18:

[0086] In order to realize the frequency modulation of infrared-terahertz microwaves, Nd x Sm 1-x NiO3 (0≤x≤1) is coated with alumina balls with diameters of 30μm to 3mm and arranged as follows Fig.12 The multilayer array of the schematic diagram is then connected to sensors and processors to complete the reception and processing of information. 0.25 Sm 0.75 NiO3 coated alumina beads with a diameter of 100 μm, using nickel oxide, neodymium oxide, and praseodymium oxide as precursors, potassium chloride as molten salt, reacted at 6 MPa and 800 degrees Celsius for 36 hours; 0.75 Sm 0.25 NiO3 coated alumina beads with a diameter of 50 μm, using nickel oxide, neodymium oxide, and praseodymium oxide as precursors, potassium chloride as molten salt, reacted at 5 MPa and 800 degrees Celsius for 24 hours; 0.5 Sm 0.5 NiO3 coated alumina beads with a diameter of 300 μm, using nickel oxide, neodymium oxide, and praseodymium oxide as precursors, potassium chloride as molten salt, reacted at 6 MPa and 900 degrees Celsius for 48 hours; 0.33 Sm 0.67NiO3-coated alumina beads with a diameter of 500μm, using nickel oxide, neodymium oxide, and praseodymium oxide as precursors and potassium chloride as molten salt, reacted at 7 MPa and 900 degrees Celsius for 36 hours; frequency modulation of infrared-terahertz microwaves from incident to reflection and transmission can be achieved, and the frequency modulation range can be calculated and adjusted by regulating the rare earth element composition to control the metal insulator phase transition temperature of the coating layer and the particle size of the beads.

[0087] Example-19:

[0088] In order to realize the compound eye position detection sensor in the infrared band, Pr x Nd 1-x NiO3 (0≤x≤1) is coated with alumina balls with a diameter of 1μm to 1mm and arranged as follows Fig.13 The hemispherical shape of the schematic diagram is then connected to the sensor and processor to complete the reception and processing of information. 0.5 Nd 0.5 NiO3 coated alumina beads with a diameter of 100 μm, using nickel oxide, neodymium oxide, and praseodymium oxide as precursors, potassium chloride as molten salt, reacted at 6 MPa and 800 degrees Celsius for 36 hours; to prepare Pr 0.2 Nd 0.8 NiO3 coated alumina beads with a diameter of 50 μm, using nickel oxide, neodymium oxide, and praseodymium oxide as precursors, potassium chloride as molten salt, reacted at 5 MPa and 800 degrees Celsius for 24 hours; to prepare Pr 0.3 Nd 0.7 NiO3 coated alumina beads with a diameter of 300 μm, using nickel oxide, neodymium oxide, and praseodymium oxide as precursors, potassium chloride as molten salt, reacted at 6 MPa and 900 degrees Celsius for 48 hours; 0.6 Nd 0.4 NiO3-coated alumina beads with a diameter of 500μm use nickel oxide, neodymium oxide, and praseodymium oxide as precursors and potassium chloride as molten salt, and react at 7 MPa and 900 degrees Celsius for 36 hours. The compound-eye position detection sensing function in the infrared band can be realized, and the metal insulator phase transition temperature of the coating layer and the particle size of the beads can be controlled by regulating the rare earth element composition to adjust the detection and reception infrared wavelength range.

[0089] Example-20:

[0090] In order to achieve non-contact triggering of electronic phase transition of rare earth nickelate by alternating magnetic field, magnetic particles are filled into the interior of alumina spheres. The heat generated by eddy current and hysteresis of magnetic particles under alternating magnetic field is used to raise the core temperature to the ReNiO3 phase transition temperature, thereby triggering the outer metal-insulator transition. x Sm 1-xNiO3 (x=0.1, 0.2, 0.3, 0.4), SmNiO3, EuNiO3, GdNiO3 are coated with magnetic particle / alumina composite spheres with a curvature radius of 50μm to 8mm. To prepare PrNiO3 coated composite spheres with a diameter of 200μm, nickel oxide and praseodymium oxide are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 6 MPa and 800 degrees Celsius for 24 hours; to prepare NdNiO3 coated composite spheres with a diameter of 150μm, nickel oxide and samarium oxide are used as precursors, potassium chloride is used as molten salt, and the reaction is carried out at 6 MPa and 800 degrees Celsius for 30 hours; to prepare Nd x Sm 1-x NiO3 (x = 0.1, 0.2, 0.3, 0.4) coated composite spheres with a diameter of 100 μm, using nickel oxide, neodymium oxide, samarium oxide as precursors, potassium chloride as molten salt, reacting at 6 MPa 800 degrees Celsius for 36 hours; to prepare SmNiO3 coated composite spheres with a diameter of 700 μm, using samarium nitrate and nickel nitrate as precursors, potassium chloride as molten salt, reacting at 9 MPa 900 degrees Celsius for 36 hours; to prepare EuNiO3 coated composite spheres with a diameter of 2 mm, using europium acetate and nickel acetate as precursors, sodium chloride as molten salt, reacting at 10 MPa 900 degrees Celsius for 36 hours. To prepare GdNiO3 coated composite spheres with a diameter of 1 mm, using gadolinium nitrate and nickel nitrate as precursors, lithium chloride as molten salt, reacting at 12 MPa 1000 degrees Celsius for 48 hours. Under the action of an external alternating magnetic field, the magnetic particles generate heat and the temperature rises below the metal-insulator phase transition temperature, and the rare earth nickelate presents an insulating phase; when the temperature rises above the metal-insulator phase transition temperature, the rare earth nickelate transforms into a metallic phase. By regulating the rare earth element composition and growth time to control the metal-insulator phase transition temperature, a non-contact external field-triggered metal-insulator phase transition can be achieved.

Claims

1. A method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material, characterized in that: The following steps are involved: 1) Design the material composition, electronic phase transition characteristics, and synergistic mode of rare earth nickelates with the functions of the core materials according to the application scenarios, select the composition, surface shape and curvature, and size of the core materials, and improve their surface chemical adsorption on rare earth nickelates in the thermodynamically metastable phase in molten salts through surface modification; 2) According to the stoichiometric ratio of the metal elements in the selected rare earth nickelate oxide, weigh the corresponding nickel and rare earth element precursor powders, add a certain proportion of molten salt and mix them evenly, apply the above-prepared mixed powder on the outside of the core material in step 1) or place the core material in the above-prepared mixed powder and compact it; 3) Heating in a strong oxidizing atmosphere allows the precursor powder to be evenly mixed in the molten salt, and reducing the original positive Gibbs free energy of the rare earth nickelate through chemical adsorption on the surface of the core material, thereby nucleating and growing a rare earth nickelate polycrystalline coating layer on the surface of the core material. After cooling, the prepared composite material consisting of the rare earth nickelate polycrystalline layer coating the core material is taken out and washed with a solvent to remove the residual flux.

2. The method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material according to claim 1, characterized in that: The crystal structure of the rare earth nickelate includes 113-type perovskite ReNiO3 and layered perovskite Re n + 1Ni n O 3n+1 ; For ReNiO3, its rare earth element Re sites include: praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y) and the common occupation of the above elements in different proportions; For the layered perovskite structure Re n +1 Ni n O 3n+1 , which mainly include Re2NiO4, Re3Ni2O7, Re4Ni3O 10 , and its rare earth elements Re positions include: lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y) and the common occupation of the above elements in different proportions.

3. The method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material according to claim 1, characterized in that: The nickel and rare earth element precursor powders include nickel oxides, nitrates, acetates and carbonates, and rare earth element oxides, nitrates, acetates and carbonates.

4. The method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material according to claim 1, characterized in that: The molten salt includes: potassium chloride (KCl), sodium chloride (NaCl), lithium chloride (LiCl), potassium carbonate (K2CO3), sodium carbonate (Na2CO3) or a mixture thereof.

5. The method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material according to claim 1, characterized in that: The functional properties of the core material can be further designed or hollowed out to fill in a functional material body, so as to coordinate the composite of the functional properties of the rare earth nickelate coating layer; the core material functions include: high infrared emissivity, microwave absorption, electromagnetic induction, ferroelectricity, and high dielectric properties; the composite of the rare earth nickelate coating layer and the core functional properties mainly includes two ways: 1) Using an external field to trigger the metal-insulator phase change characteristics of the rare earth nickelate coating layer to achieve reversible shielding of the core function; the external field includes temperature, polarization electric field, light triggering, and atmosphere triggering; 2) The reversible triggering of the metal-insulator phase change of the rare earth nickelate coating layer is triggered by the coupling of the inner core layer and the external field, thereby realizing the sudden change of the overall optical and electrical properties of the nickelate-coated inner core composite material; the external field includes an alternating electric field and an alternating magnetic field; through the synergy of the above-mentioned functional characteristics of the inner core material and the electronic phase change characteristics of the rare earth nickelate, the intelligent triggering design of the overall functions of critical microwave power, electromagnetic induction, intelligent electromagnetic shielding under polarized electric field triggering, optical design and infrared camouflage, infrared emissivity regulation, and infrared reflectivity regulation can be realized.

6. The method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material according to claim 1, characterized in that: The rare earth sites of the above perovskite and layered perovskite can be partially replaced by alkaline earth element Ae, or the Ni-site can be partially replaced by other transition elements, so as to further regulate the valence state of nickel element, the electronic structure of the material, the electrical transport properties, and the magnetism in the rare earth nickelate coating layer; wherein, the alkaline earth element Ae includes calcium, strontium, and barium; Re 2-x Ae x NiO4, Re 3- x Ae x Ni2O7, Re 4-x Ae x Ni3O 10 The substitution range of the alkaline earth element in it is 0 < x ≤ 1, Re 1-x Ae x The substitution range of the alkaline earth element in NiO3 is 0 < x ≤ 0.3; the other transition elements are preferably manganese, iron, rhenium, vanadium, and cobalt, and their substitution range for Ni-elements is greater than 0 and less than or equal to 30%.

7. The method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material according to claim 1, characterized in that: The core material components include aluminum oxide, titanium oxide, zirconium oxide, hafnium oxide, and garnet ferrite. Its forms include single crystal and polycrystalline ceramic body. Its curved surface shapes include sphere, ellipsoid, and cylinder. Its typical size ranges from 1 micron to 1 centimeter.

8. The method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material according to claim 1, characterized in that: The external field triggering forms of the electronic phase change characteristics of the rare earth nickelate coating layer include: ambient temperature triggering, applied polarization electric field triggering, chemical environment triggering, applied stress triggering, and core material coupling triggering. The electronic phase change triggering external field threshold range is regulated by adjusting the composition, curvature radius, thickness of the rare earth nickelate coating layer, and the composite design with the core material.

9. The method for preparing a rare earth nickelate electronic phase change oxide curved surface coating composite material according to claim 1, characterized in that: The prepared rare earth nickelate curved surface coated core composite material can be further arranged into an array, and the overall optical properties, microwave transmission properties, and DC and AC electric transport properties before and after the electronic phase change can be adjusted by regulating the array arrangement.

10. Application of the rare earth nickelate electronic phase change oxide curved surface coating composite material prepared by the method according to claim 1, characterized in that: Aluminum oxide, titanium oxide, zirconium oxide, hafnium oxide, and garnet ferrite with a certain curved surface shape are used as the core and their surface is modified to improve the surface adsorption effect on the specific crystal plane of rare earth nickelate oxide. After mixing with rare earth, nickel element precursors and specific flux, a rare earth nickelate polycrystalline layer is used to coat the surface of the above-mentioned core that does not have a crystal coherent relationship through a flux reaction; the metal-insulator transition characteristics of the prepared composite material and the functional characteristics of the core material can achieve multi-dimensional functional response under the design and regulation of external field. The shell layer of the composite material with a core-shell structure has the functional characteristics of electronic phase change under external field triggering, and can cooperate with the functional characteristics of the core material, thereby realizing intelligent electromagnetic shielding, optical design and infrared camouflage, optical anti-counterfeiting, external field sensitive resistors, logic electronic devices, and catalytic functions.

Citation Information

Patent Citations

  • Synthesis method of metastable-state rare-earth nickel-based perovskite oxide powder material

    CN109503165A

  • Composite modification method for strength of rare earth nickel-based oxide electronic phase change material

    CN114436655A

  • Hydro-induced electron phase change dynamic regulation and control method for metastable-phase rare earth nickel-based oxide

    CN115144441A

  • Preparation method of rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material

    CN116903369A

Cited By

  • Rare earth nickelate wave-absorbing material and preparation method thereof

    CN121377721A

  • Molten salt assisted oxygen partial pressure self-adjusting intermediate valence transition group oxide preparation method

    CN121449099A